Anemia Management Model in Pulmonary Tuberculosis Using Beetroot and Tomato Combined With A High-Calorie and High-Protein Diet - Evarina Sembiring; Henny Syapitri; Amila Amila (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Beetroots and tomatoes are rich In vitamins, iron, folic acid, and other nutrients that can be used as an alternative in treating anemia. High protein and calorie intake dietary is necessary to improve patients’ nutritional status in pulmonary tuberculosis. The purpose was to examine the effect of beetroot juice consumption, tomato juice combined with a high protein and calorie diet on hemoglobin pulmonary tuberculosis. This research was an analytical comparative with quasi-experimental design by pre-test and post-test control group design. This study was conducted to 45 patients of Pulmonary tuberculosis who having anti-TB treatment at Pulmonary Policlinic Sari Mutiara Medan General Hospital, using purposive sampling technique, divided into three treatment groups. All of the treatments were administered for 30 days, pre and post-treatment were given the hemoglobin test. Data were analyzed by using paired t-test and One Way Anova, followed by Linear Regression. All of three group treatments are having an increasing level of  hemoglobin, mean hemoglobin level in Group I:  2.5 gr/dl, p-value = 0.000., Group II: 1.8 gr/dl. p-value = 0.002. , Control group It:  1.1 gr/dl, p-value = 0.004.Beetroot juice with a diet high in proteins and calories most effective to increase levels of hemoglobin and nutritional status in pulmonary tuberculosis, this intervention can be recommended as a  management modeling of anemia in pulmonary TB patients who received anti-TB treatment. Abstrak: Bit dan tomat kaya dengan vitamin,zat  besi,asam folat dan nutrisi lainnya dapat digunakan sebagai alternatif dalam mengobati anemia. Diet tinggi protein dan kalori diperlukan untuk meningkatkan status gizi pasien tuberkulosis paru. Tujuan penelitian adalah untuk menguji pengaruh konsumsi jus bit,jus tomat yang dikombinasikan dengan diet tinggi protein dan kalori terhadap hemoglobin tuberkulosis paru. Jenis penelitian ini adalah analitik komparatif dengan desain squasi eksperimen pre test  dan post test kontrol. Penelitian ini dilakukan terhadap 45 penderita TB Paru dengan program pengaoabatan  anti TB di Polikilinik  Paru RSU Sari Mutiara ,menggunakan tehnik purposive sampling yang dibagi menjadi 3 kelompok perlakuan.  Semua kelompok dilakukan treatmen selama 30 hari,sebelum dan sesudah treatmen dilakukan pemeriksaan hemoglobin. Analisa data menggunakan uji t berpasangan dan One way Anova dilanjutkan dengan Regresi Linier. Hasil penelitian didapatkan ketiga kelompok perlakuan mengalami peningkatan  kadar hemoglobin, rerata kadar hemoglobin pada  kelompok I: 2.5 gr/dl p .value= 0.00, Kelompok II: 1.8 gr/dl. p-value= 0.002, Kelompok Kontrol: 1.1 gr/dl, p-value= 0.004. Jus bit dengan diet tinggi protein dan kalori paling efektif untuk meningkatkan kadar hemoglobin dan status gizi pada tuberkulosis paru, Intervensi ini dapat direkomdasikan sebagai model dalam managani anemia pada tuberkulosis paru. dengan program pengobatan tanti TB (OAT).